Cloth Mask with Window as an Alternative to Opaque Mask for Students with Speech, Language, and Hearing Deficits for Infection Risk Mitigation - Kim, Yang-Seon; Deepthi Markonda Patnaik, Aruna; Teran, Paul; Pandeya, Pratik; Kuhlmann, Stephanie; Dedeaux, Julian; Harris, Kari (Kansas Journal of Medicine, 2025)
Introduction. Visualization of oral movements and facial expressions is essential for learning, development, and communication, especially among students receiving speech and language services. This study aimed to assess the effectiveness of cloth masks with transparent windows as an alternative to opaque masks in mitigating the risk of droplet-transmitted infectious diseases. Methods. Researchers measured the filtration efficiency of various medical and non-medical masks, both with and without transparent windows. A testing pipe, fitted with the selected masks, was used to deliver particulate matter (PM) at an airflow velocity mimicking human breathing. Particle size and airflow were measured using three real-time particle monitors positioned upstream and downstream of the masks. Filtration efficiency was then calculated for each of the eight masks.Results. Mask efficiency varied based on build quality and material. Filtration efficiency for the four face masks with transparent windows ranged from 28.6% to 90%, with the single-layer mask performing the worst. All multi-layer masks with windows achieved filtration efficiencies greater than 70% for all particle sizes tested (1, 2.5, and 10 microns), exceeding that of the opaque cotton masks and approaching the filtration levels of surgical masks.  Conclusions. Given the high filtration efficiency of cloth masks with transparent windows, the authors conclude that these masks can reduce the transmission of SARS-CoV-2 and other droplet-transmitted infectious diseases while also improving communication for individuals with speech, language, and/or hearing impairments.